2012
DOI: 10.1111/j.1551-2916.2012.05231.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Bond Ionicity, Lattice Energy, and Microwave Dielectric Properties of Zn(Ta1−xNbx)2O6 Ceramics

Abstract: The crystalline structure refinement, chemical bond ionicity, and lattice energy were carried out for Zn(Ta1−xNbx)2O6 ceramics with tri‐α‐PbO2 structure to investigate the correlations between the crystalline structure, phase stability, bond ionicity, and microwave dielectric properties. The chemical bond ionicity and lattice energy of the ZnTa2O6 system were calculated and evaluated using a semiempirical method based on the dielectric description theory proposed by Phillips, Van Vechten, and Levine (P–V–L the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(32 citation statements)
references
References 25 publications
(59 reference statements)
0
32
0
Order By: Relevance
“…The liquid hole transmitting medium (HTM) was recently replaced by solid HTM for long term stability of the solar cell by a Korean group, and they reported an efficiency of 17.9% [145]. Recently, slightly over 20% efficiency was claimed to be achieved with a solid state CH 3 NH 3 PbX 3 based solar cell device [146]. The organometallic halide perovskite absorbers have better properties than metal chalcogenide quantum dots, though they have the same absorption coefficient [120,136].…”
Section: Zno Nanowiresmentioning
confidence: 99%
“…The liquid hole transmitting medium (HTM) was recently replaced by solid HTM for long term stability of the solar cell by a Korean group, and they reported an efficiency of 17.9% [145]. Recently, slightly over 20% efficiency was claimed to be achieved with a solid state CH 3 NH 3 PbX 3 based solar cell device [146]. The organometallic halide perovskite absorbers have better properties than metal chalcogenide quantum dots, though they have the same absorption coefficient [120,136].…”
Section: Zno Nanowiresmentioning
confidence: 99%
“…Next, Zhang further developed the theory by expanding its application to include more complex compounds by seperating complex compounds A a B b C c D d into binary crystals A m B n . For instance, binary expressions of tri‐α‐PbO 2 structured ZnTa 2 O 6 have been reported by Xia, including the different crystal structure, coordinate environment, site occupancy and bond types using its unique binary bonding subformula. Hence, the binary expressions of ZnNb 2 O 6 are identified based on its crystal structure, coordinating environments and charge distribution of ions, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Lattice energy ( U ) is a concept indicating the binding abilities between ions . A structure shows high stability in the presence of strong binding ability . The U value is calculated based on the following:UTotal=false∑μUcμ+UiμkJ/mol U c μ = 2100 m Z + μ 1.64 d μ 0.75 f c μ kJ/mol Uiμ=1270m+nZ+μZ-μdμ0.751-0.4dμfiμkJ/mol,where U total , Ucμ and Uiμ are total lattice energy, covalent part and ionic part of lattice energy, respectively, m and n are the parameters in A m B n binary expressions, and Z+μ and Z-μ reflect the valence state of Zn 2+ and Nb 5+ cations and O 2− anion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations suggest that the internal electrical fields associated with microscopic polarization domains contribute to hysteretic anomalies in the current–voltage response of PSCs due to variations in electron–hole recombination in the bulk [110]. However, others would suggest that, due to its low lattice energy, organometal halide perovskite tends to possess strong ionic characteristics, which are sensitive to polarization in an electric field [111]. An impedance study has shown that a high value of the dielectric constant at low frequencies results from a combination of dipolar, ionic and electronic contributions, which are the main reasons for the J / V hysteresis [112115].…”
Section: More Exciting Discoveries and Open Issuesmentioning
confidence: 99%